The Correlation of Collateral Circulation and Age during Acute Ischemic Heart Disease - Chigogidze, Maia; Sharashidze, Nino; Pagava, Zurab; Taboridze, Iamze (European Scientific Journal, ESJ, 2020)
Backgroundː Coronary collaterals (CC) are alternative sources of blood supply to myocardium jeopardized by Ischemia. Aim: To investigate the dependence and influence of collateral circulation on age during acute ischemic heart disease. Methods: Analysis shows that 673 patients were studied from the SamgoriMedi Clinic (Tbilisi, Georgia) aged 27– 94 years (64.7+11.48) with acute coronary syndromes. Basic medical data such as sex, age, cardiovascular risk factors, angina pectoris, revascularization history, echocardiography, and laboratory data were obtained from the patient’s medical records. CC vessels were graded according to the Rentrop grading system of 0 to 3. Resultsː The development index of collateral circulations visibly increases with age. Average age increases accordingly as follows: rentrop 0 - 62.85+12.01, rentrop 1 - 64.90+10.79, rentrop 2 - 66.84+10.49, and rentrop 3 - 69.04+9.68 (p<0.0001). There is positive significant correlation between the development of collateral circulation and age groups r=0.170**, p<0.001. The cases of female sex, hypertension, acute MI without ST elevation, CABG frequency (also EF% - 35-45%, <35%), and multiple vessel coronary lesion are noticed to increase with age, while the male sex and EF (ejection fraction) >45% cases decreases with age. Conclusion Collateral circulation shows significantly positive correlation with age and female sex. However, it should be mentioned that in elderly patients with a high ejection fraction and normal diastolic function, the development of collateral vessels is low.